Revalensi Malnutrisi Pada Lanjut Usia Berdasarkan Mini Nutrisional Assesment-Short Form (MNA-SF) - Purwantini, Dwi; Prasetya, Widya; Saputra, Agung Kurniawan (STIKes Panti Rapih, 2024)
Malnutrition is a clinical condition resulting from an imbalance between the need, intake, and utilization of nutrients, resulting in increased morbidity and mortality rates, as well as decreased quality of life. Malnutrition is common in the elderly. The purpose of this study was to determine the prevalence of malnutrition in the elderly based on the Mini Nutritional Assessment-Short Form (MNA-SF) at the Surabaya Elderly Posyandu. The research design was a descriptive study using a questionnaire as a data collection tool. The target population in this study was the elderly aged ≥60 years at the Surabaya Elderly Posyandu, totaling 61 elderly. The sampling technique was total sampling. Data were collected by filling out the Mini Nutritional Assessment-Short Form (MNA-SF) questionnaire. The results of the study showed that the nutritional status of the elderly based on the MNA-SF was 46 elderly (75.4%) with normal nutritional status, 14 elderly (23%) with nutritional status at risk of malnutrition and 1 elderly (1.6%) with malnutrition nutritional status